Effect of consumer self‐confidence on information search and dissemination: Mediating role of subjective knowledge. (25th October 2018) - Utkarsh; Sangwan, Sunanda; Agarwal, Pallavi
Abstract: Consumers search for information about products to make a satisfactory purchase decision and gain knowledge about new features and updates. Consumers also use this knowledge to be vocal about their product experience because several consumers seek interpersonal recommendations. This phenomenon has contributed to the emergence of information search (IS) and information dissemination (ID) as a key research area in the field of consumer behaviour. However, the role of personal factors such as consumer self‐confidence and subjective knowledge has received little attention in the extant IS and ID literature. The major argument of this study is that information acquisition confidence and social outcome confidence enhance subjective knowledge and consequently increase the will of consumers to search and disseminate information in the context of smartphone buyers in India. Structural equation modelling was employed to test the proposed hypotheses using a convenience sample of 259 consumers obtained through a cross‐sectional survey. The study shows that subjective knowledge is crucial in strengthening the association between consumer self‐confidence and consumer intention for IS and ID. Additionally, enhancing consumer's social outcome confidence contributes towards high subjective knowledge and consequently accelerates information dissemination. Results suggest that firms could focus on enhancing the social outcome confidence and subjective knowledge of consumers to motivate them to disseminate information. The results also show that consumers with high confidence in information acquisition ability have the high subjective knowledge and are more likely to search for information. Overall, this study contributes to the emerging literature regarding the role of personal factors in IS and dissemination behaviour.